Five-year incidence, progression and risk factors for age-related macular degeneration: The Age, Gene/Environment Susceptibility Study - Jonasson, Fridbert (2014)
OBJECTIVE: To investigate the incidence and progression of age related m acular degeneration (AMD) and associated risk factors. DESIGN: Population-based prospective cohort study. PARTICIPANTS: 2868 participants from the Age Gene/Environment Susceptibility-Reykjavik Study with retinal data at baseline and five-year follow-up. METHODS: Digital macular photographs were graded for presence of AMD. Participants completed a questionnaire and extensive clinical battery. Biomarkers were assessed. Risk factors for AMD were analyzed using multivariate regression analysis with odds ratios (ORs) and 95% confidence intervals (CIs). MAIN OUTCOME MEASURES: AMD, defined as early or late. RESULTS: Among 2196 participants free of AMD at baseline, 14.9% developed incident AMD. In multivariate models, incident AMD was significantly associated with age (OR per year 1.14 (95% CI 1.11, 1.17)), current smoking (OR 2.07 (1.38, 3.11)), former smoking (OR 1.36 (1.04, 1.79)), plasma high-density lipoprotein (HDL) cholesterol level (OR 1.62 per mmol/L (1.19, 2.22)), and body mass index (BMI) (OR 1.04 per kg/m(2) (1.01, 1.07)). Among 563 participants with early AMD at baseline, 22.7% progressed to late AMD (11.0% pure geographic atrophy (GA) and 11.7% exudative AMD). In multivariate analyses, age was significantly associated with progression to GA (OR 1.14 (1.07, 1.21)) and exudative AMD (OR 1.08 (1.01, 1.14)). Adjusting for age, female sex was associated with exudative AMD (OR 2.10 (1.10, 3.98)) and plasma HDL cholesterol with GA (OR 2.03 per mmol/L (1.02, 4.05)). CONCLUSION: By age 85 years, 57.4% of participants had signs of AMD. Age, smoking, plasma HDL cholesterol, BMI and female sex are associated with AMD. Elevated HDL cholesterol is associated with GA development.